1989
DOI: 10.1093/clinchem/35.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral calcinosis: seasonal biochemical studies and chemical studies of eyelid lesion.

Abstract: We recently described (Arch Ophthalmol 1988; 106:725-6) the presence of unique calcific lesions in the eyelids of a young woman with a history of hyperphosphatemic tumoral calcinosis. Here we document that no immediate family members showed similar lesions and that none was hyperphosphatemic. Dental roentgenography revealed characteristic abnormalities in the patient that confirmed the clinical diagnosis of tumoral calcinosis. Seasonal biochemical studies demonstrated persistently increased concentrations of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On computed tomography (CT), the appearance of the calcified masses varies from small and solid in some patients to large and cystic in other patients (7); in magnetic resonance imaging (MRI), they display high signal intensity on T2 weighted images (7). Panoramic dental radiograms reveal pathognomonic dental abnormality of short bulbous bulbous roots and partial obliteration of pulp cavities, which strongly support the diagnosis (7,12,20,24,25).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…On computed tomography (CT), the appearance of the calcified masses varies from small and solid in some patients to large and cystic in other patients (7); in magnetic resonance imaging (MRI), they display high signal intensity on T2 weighted images (7). Panoramic dental radiograms reveal pathognomonic dental abnormality of short bulbous bulbous roots and partial obliteration of pulp cavities, which strongly support the diagnosis (7,12,20,24,25).…”
Section: Discussionmentioning
confidence: 92%
“…Laboratory findings, including serum calcium concentration, parathyroid hormone, renal function, and alkaline phosphatase, are normal. Some investigators have reported however an association with variably elevated serum phosphorous levels (1,2,7,(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic calcinosis cutis includes tumoral calcinosis which predominantly involves the joints and ocular involvement is rare,[ 4 ] and subepidermal calcinosis involves mostly the head and neck region including the ocular adnexa. [ 3 5 ] Serum calcium and phosphorus levels are normal in dystrophic calcinosis and deranged in metastatic variants and calciphylaxis. Idiopathic variants may or may not show such serum abnormalities.…”
Section: Discussionmentioning
confidence: 99%